Strategi Memahami Berita Media melalui Telaah Model Ruang Redaksi, Teori Konsensus dan Teori Kepanikan Moral (Program Studi Ilmu Administrasi Bisnis, 2014)
The purpose of this article is to describe and analyze several models and theories about media newsroom. Through theoretical review, this article could be the strategy in understanding how news produced by the media. Further description cover up study of newsroom models (gatekeeping and process model), theory of influences on mass media content, theory of media and consensus, theory of moral panic and theory of public interest. The significancy of this article imply the significant of advance research on framing effects by media and more objective on beyond of the news. In the context of public interest, do media work for public interest or deal with ideological state apparatus or ideological business apparatus. Keywords: media, newsroom, media concensus, moral panic, public interest.